Quelques notes sur la réforme de la détermination de la peine au Canada - Brodeur, Jean-Paul (Criminologie)

(untitled) (Les Presses de l'Université de Montréal, 1991)
This review of recent developments in the field of sentencing in Canada begins by observing that none of the recommendations of the Canadian Sentencing Commission were implemented, since the commission issued its report in 1987. This amounts to a prolongation of the status quo. We propose elements of explanation as to why there was no follow up to the Commission's proposals. Second, we present a critical analysis of the latest consultation package on sentencing and parole, that was put together by the federal Department of Justice in 1990. We argue that the proposed statement of purposes and principles of sentencing should priorize the different sentencing goals that it enumerates. We also point out that there is an unbalance between the sentencing and parole components of the permanent commission proposed by the Department of Justice. The sentencing component is required to make sentencing policy, whereas the parole component acts as an advisor to the National Parole Board.